Alternative Treatment of Psychological Disorders Such as Spider Phobia Through Virtual Reality Environments. - Armas Naranjo, Joseph Eduardo (2018)
This article proposes a tool to support the psychotherapist in the process of treating spider phobia through a system that combines both software and hardware elements to present immersive virtual reality environments to the treated patient. To create the feeling of immersion, environments and models created in Unity are used in conjunction with the patient’s movement tracked through the Kinect motion sensor. For the development of the system, the psychotherapeutic treatment method of systematic desensitization is used, so that the patient can overcome his fear and present non-phobic interactions with spiders. The process of developing the system and redacting this document was supported and supervised by a psychologist specialized in the treatment of phobias. Finally, tests were performed to obtain feedback from specialists and potential patients with a medium degree of phobia, in which the results were very positive and satisfactory.